Bounded Irregular Pyramid: a new structure for color image segmentation. - Marfil-Robles, Rebeca; Rodríguez-Fernández, Juan Antonio; Bandera-Rubio, Antonio Jesús; Sandoval-Hernández, Francisco (Elsevier, 2003)
This paper presents a new segmentation technique for color images. It relies on building an irregular pyramid into a regular one, presenting only nodes associated to homogeneous color regions. Hence, the size of the irregular pyramid is bounded. Segmentation is performed by rearranging the set of links among pyramid nodes. Unlike other hierarchical methods based on relinking procedures, our algorithm does not operate in an iterative way and it preserves region connectivity.
Keywords: Procesado de imágenes - Técnicas digitales; Color segmentation; Pyramidal structure